Ankylosing spondylitis and psoriatic arthritis: revisiting screening of latent tuberculosis infection and its follow-up during anti-tumor necrosis factor therapy in an endemic area - Andrea Yukie Shimabuco; Ana Cristina de Medeiros-Ribeiro; Renata Miossi; Karina Rossi Bonfiglioli; Julio Cesar Bertacini de Moraes; Celio Roberto Gonçalves; Percival Degrava Sampaio-Barros; Claudia Goldenstein-Schainberg; Fernando Henrique Carlos de Souza; Leandro Lara do Prado; Michele Remião Ugolini-Lopes; Emily Figueiredo Vieira Neves Yuki; et al. (Clinics, 2020)
OBJECTIVES: To retrospectively evaluate the performance and distinctive pattern of latent tuberculosis (TB) infection (LTBI) screening and treatment in patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA) under anti-tumor necrosis factor (TNF) therapy and determine the relevance of re-exposure and other risk factors for TB development. METHODS: A total of 135 and 83 patients with AS and PsA, respectively, were evaluated for LTBI treatment before receiving anti-TNF drugs via the tuberculin skin test (TST), chest radiography, and TB exposure history assessment. All subjects were evaluated for TB infection at 3-month intervals. RESULTS: The patients with AS were more often treated for LTBI than were those with PsA (42% versus 30%, p=0.043). The former also presented a higher frequency of TST positivity (93% versus 64%, p=0.002), although they had a lower frequency of exposure history (18% versus 52%, p=0.027) and previous TB (0.7% versus 6%, p=0.03). During follow-up [median, 5.8 years; interquartile range (1QR), 2.2-9.0 years], 11/218 (5%) patients developed active TB (AS, n=7; PsA, n=4). TB re-exposure was the main cause in seven patients (64%) after 12 months of therapy (median, 21.9 months; IQR, 14.2-42.8 months) and five LTBI-negative patients. TB was identified within the first year in four patients (36.3%) (median, 5.3 months; IQR, 1.2-8.8 months), two of whom were LTBI-positive. There was no difference in the TB-free survival according to the anti-TNF drug type/class; neither synthetic drug nor prednisone use was related to TB occurrence (p>0.05). CONCLUSION: Known re-exposure is the most critical factor for incident TB cases in spondyloarthritis. There are also some distinct features in AS and PsA LTBI screening, considering the higher frequency of LTBI and TST positivities in patients with AS. Annual risk reassessment taking into consideration these peculiar features and including the TST should be recommended for patients in endemic countries.